A Moderate Blast Exposure Results in Dysregulated Gene Network Activity Related to Cell Death, Survival, Structure, and Metabolism - Edwards, Katie A.; Motamedi, Vida; Osier, Nicole D.; Kim, Hyung-Suk; Yun, Sijung; Cho, Young-Eun; Lai, Chen; Dell, Kristine C.; Carr, Walter; Walker, Peter; Ahlers, Stephen; LoPresti, Matthew; et al. (Frontiers in Neurology, 2020)
Blast exposure is common in military personnel during training and combat operations, yet biological mechanisms related to cell survival and function that coordinate recovery remain poorly understood. This study explored how moderate blast exposure influences gene expression; specifically, gene-network changes following moderate blast exposure. On day 1 (baseline) of a 10-day military training program, blood samples were drawn, and health and demographic information collected. Helmets equipped with bilateral sensors worn throughout training measured overpressure in pounds per square inch (psi). On day 7, some participants experienced moderate blast exposure (peak pressure ≥5 psi). On day 10, 3 days post-exposure, blood was collected and compared to baseline with RNA-sequencing to establish gene expression changes. Based on dysregulation data from RNA-sequencing, followed by top gene networks identified with Ingenuity Pathway Analysis, a subset of genes was validated (NanoString). Five gene networks were dysregulated; specifically, two highly significant networks: 1. Cell death and survival (score: 42), including 70 genes, with 50 downregulated and 2. Cell structure, function, and metabolism (score: 41), including 69 genes, with 41 downregulated. Genes related to ubiquitination, including neuronal development and repair: UPF1 (UPF1, RNA Helicase and ATPase) was upregulated while UPF3B (UPF3 Regulator Of Nonsense Transcripts Homolog B) was downregulated. Genes related to inflammation were upregulated, including AKT1, a gene coordinating cellular recovery following TBIs. Moderate blast exposure induced significant gene expression changes including gene networks involved in 1) cell death and survival and 2) cellular development and function. The present findings may have implications for understanding blast exposure pathology and subsequent recovery efforts.